E-business Conditions and Perspectives in Lithuanian Enterprises - Jucevičienė, Vilija (Ekonomika, 2003)
The article analyses e-business experience and perspectives in agricultural, trading, service and production enterprises in Lithuania. The analysis of literature sources discusses the e-business concept. e-business partners (business, consumer, administration and employees) and communication among them. It analyses the advantages (cost, customer, competition) and shortcomings of e-business (law, security and cost). The practical research of e-business applications and perspectives (hardware, software, internet and data structures) is based on studies of enterprises in Lithuania during 2002.